SUCCESSFUL MANAGEMENT OF HYDRALLANTOIS IN A MID-GESTATION GIR COW- A CASE REPORT - ABARNA, M; PUGAZHARASI, C; NAVANEETHAKRISHNAN, S; ARUNAMAN, C S; SURESHKUMAR, R; ARUNMOZHI, N; JOSEPH, CECILIA; SARATH, T (The Indian Journal of Animal Reproduction, 2020)
A pluriparous Gir cow was presented to the Large Animal Outpatient Medicine Unit of Madras Veterinary College Teaching Hospital with the history of anorexia, distended abdomen and scanty dung for the past one week. On clinical examination, bilateral distension of abdomen was observed. Per-rectal examination revealed severely distended uterus with prominent fremitus. Sonographic examination revealed presence of fluid filled sacs with intermittently moving foetus, cranial displacement of abdominal organs and severe hepatic congestion. The condition was diagnosed as hydrallantois based on per-rectal findings and ultrasound examination. Hence, the pregnancy was terminated using intramuscular injection of Cloprostenol sodium @ 500μg and Dexamethasone @ 24mg. After 20 hours of treatment, the cow had expelled around 80-100 litres of yellowish, serous fluid along with a live 5 months old male foetus without any abnormality or congenital deformity which died within an hour and the cow had recovered imperceptibly.